Impact on E-Commerce Adoption on Entrepreneurial Orientation and Market Orientation in Business Performance of SMEs - Octavia, Ade; Indrawijaya, Sigit; Sriayudha, Yayuk; Heriberta; Hasbullah, Husni; Asrini (Asian Economic and Financial Review, 2020)
In the industrial ERA 4.0, changes digitally and physically are inevitable, as well as for small to medium enterprise (SMEs). The majority of SMEs in Jambi Province have not conducted digital technology as a marketing strategy for the expansion of its market share. The purpose of this research are: (1) analyzing the impact of entrepreneurial orientation on SME business performance, (2) analyzing the influence of market orientation with the e-commerce adoption towards SMES’s business Performance (3). interpreting the e-commerce adoption and market orientation impact to SME’s business performance. The research design uses the Mix method of qualitative and quantitative. The data is collected by primary and secondary data. The data analysis techniques uses Structural Equation Model (SEM) and ran by SmartPLS3 program. Samples of this study consist of 250 SMEs who have already used digital e-commerce technology in Jambi Province. The result of data processing indicates there is a significant influence between entrepreneurial orientation, market orientation and e-commerce adoption to SME’s business performance in Jambi Provinces. We believe that entrepreneurial orientation, market orientation and e-commerce adoption model in this study will have both managerial and academic positive implication. This study will have managerial implication for practitioners in Indonesia and other countries. Academic implications is also need for researcher who are interested in increasing SME’s business performance in term of e-commerce adoption.